The Utilization of Blockchain Technology in The Airport Industry: A Review - Aan Khunaifi; Fajaryan Wijananto; Karina M Handoyo; M. Rafi Juliansyah; M. Thufaili Imdad; Mukti Wibowo; Tanzi M Santoso; Topan Try Harmanda; Yosi Sahreza; Muhammad Arief (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2023)
Blockchain is a digital ledger technology in which transactions are stored in a continuously growing list of blocks that cannot be changed and distributed without a centralized server. In recent years, the airport industry has become one of the industries that have implemented blockchain into its business processes. For this reason, we would like to review existing research on the implementation of blockchain in the airport industry to provide an overview of how far blockchain has developed in the industry and also to identify which business processes in the airport industry can be optimized by implementing Blockchain. The review results show that there are three business processes that take place in airports, namely baggage handling systems, cargo handling, and passenger management for aircraft. Blockchain Technology can also be combined with other supporting technology, such as IoT, Artificial Intelligence (AI) / Machine Learning (ML), Big Data, etc. From the research literature that we analyzed, the combined use of blockchain technology with IoT and AI/ML can increase security in the process of data transactions in the system.